Protective Effects of Tormentic Acid on Unilateral Ureteral Obstruction-Induced Renal Injury, Inflammation, and Fibrosis: A Comprehensive Approach to Reducing Oxidative Stress, Apoptosis, and Ferroptosis - Ah Young Yang; Jung-Yeon Kim; Mi-Gyeong Gwon; Hyun Hee Kwon; Jaechan Leem; Eon-Ju Jeon (Antioxidants)
Chronic kidney disease (CKD) progresses through mechanisms involving inflammation, fibrosis, and oxidative stress, leading to the gradual structural and functional deterioration of the kidneys. Tormentic acid (TA), a triterpenoid compound with known anti-inflammatory and antioxidant properties, shows significant potential in counteracting these pathological processes. This study explored the protective role of TA in a unilateral ureteral obstruction (UUO)-induced CKD model. Mice received TA through intraperitoneal injections at a dosage of 5 mg/kg per day for 8 consecutive days, commencing a day before the UUO procedure. The TA treatment significantly improved both structural and functional kidney injury. It suppressed cytokine expression and reduced immune cell infiltration, inhibited the activation of the mitogen-activated protein kinase cascade, and alleviated endoplasmic reticulum stress. Moreover, TA displayed potent anti-fibrotic effects by reversing epithelial-to-mesenchymal transition and inhibiting Smad2/3 activation, reducing extracellular matrix deposition. TA also mitigated oxidative stress by attenuating lipid peroxidation and boosting antioxidant defenses. Additionally, it inhibited apoptosis and ferroptosis by reducing oxidative stress and modulating key cell death markers. Collectively, these findings indicate that TA provides comprehensive renoprotection in the UUO model by effectively targeting inflammation, fibrosis, oxidative stress, and tubular cell death in CKD progression.